Palaeobiology of Middle Paleozoic Marine Brachiopods A Case Study of Extinct Organisms in Classical Paleontology - Bose, Rituparna; SpringerLink (Online service) (Heidelberg : Springer International Publishing : Imprint: Springer, 2013)
Fossil species appear to persist morphologically unchanged for long intervals of geologic time, punctuated by short bursts of rapid change as explained by the Ecological Evolutionary Units (EEUs). Here, morphological variation in Paleozoic atrypide morphology at the subfamily level (Atrypinae and Variatrypinae) from the Silurian and Devonian time intervals in the third Paleozoic EEU (~444-359 my) were investigated using relatively new techniques of quantitative modeling. The study explains how a group of closely related taxa in atrypide subfamilies exhibit morphological conservation through time in P3 EEU within the Eastern North America region.
Ecological Evolutionary Units -- Patterns of Morphological Change in Fossil Lineages -- Why Atrypides -- Climate and Environment in the Silurian and Devonian -- Ecological Interactions -- Research Hypotheses -- Materials and Methods -- Geometric Morphometrics -- Data Set -- Results -- Temporal Variation -- Spatial Variation -- Mean Morphological Shape -- Encrustation Versus Morphological Shape.-Discussion -- Morphology -- Climate Setting in the Silurian and Devonian -- Atrypide Distribution.-Atrypide Diversity -- Temporal Variation -- Spatial Variation- Ecological Causes-Environmental Effect.
Keywords: Geography; Life sciences; Paleontology; Conservation biology; Earth Sciences; Paleontology; Conservation Biology/Ecology.; Biogeosciences